Comparing Single and Dual Console Systems in the Robotic Surgical Training of Graduating OB/GYN Residents in the United States. (3rd February 2016) - Mikhail, Emad; Salemi, Jason L.; Hart, Stuart; Imudia, Anthony N.
Abstract : Objective . To assess the impact of a single versus dual console robotic system on the perceptions of program directors (PD) and residents (RES) towards robotic surgical training among graduating obstetrics and gynecology residents. Design . An anonymous survey was developed using Qualtrics, a web-based survey development and administration system, and sent to obstetrics and gynecology program directors and graduating residents. Participants . 39 program directors and 32 graduating residents (PGY4). Results . According to residents perception, dual console is utilized in about 70% of the respondents' programs. Dual console system programs were more likely to provide a robotics training certificate compared to single console programs (43.5% versus 0%, p = 0.03 ). A greater proportion of residents graduating from a dual console program perform more than 20 robotic-assisted total laparoscopic hysterectomies, 30% versus 0% (p = 0.15 ). Conclusions . Utilization of dual console system increased the likelihood of obtaining robotic training certification without significantly increasing the case volume of robotic-assisted total laparoscopic hysterectomy.